The effect of exercise in pulmonary rehabilitation on the quality of life of chronic obstructive pulmonary disease patients - Brown, Jennifer Leigh (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScSportSc)--University of Stellenbosch, 2004.